The Activities of Eszterházy Károly Catholic University in the Field of Sustainability - Dr Pajtókné Tari, Dr Ilona; Váczy, Dr Kálmán; Ruszkai, Dr Csaba; Patkós, Dr Csaba; Piskóti-Kovács, Dr Zsuzsa (Journal of Sustainability Perspectives, 2023)
The Eszterházy Károly Catholic University is an innovative, service-oriented university that responds to the needs of regional economy and labor force. The University considers the sustainability as core value, the element of sustainability appears in the field of its educational, research and third mission activities.The Sustainable Development Strategy of the University was accepted in 2021, however the principles of sustainability have been appeared in the Organizational and Operational Regulations of the University dated 2016. The Sustainable Development Strategy provides the framework of activities which are contributing to reach the sustainability goals of the university. The main objective of the Article is to present these activities.